'I’m Passive yet devoted': reconstructing fan identity and hierarchy in the transcultural landscape - Zheng, Shiyu Sharon (Humanities & social sciences communications, 2025)
Fan identity is a subject of extensive discourse in the academic community without a conclusive definition. This research delves into the intricate realm of Chinese Sherlock fandom, situating the discussion within the broader context of transcultural fan studies, which uncovers the entanglement among fan identity, gender dynamics, state power and transcultureness. Through an exhaustive exploration of 45 interviews from 2019 to 2022, this article meticulously examines fan identity and its hierarchy construction within the communities. I argue that intertwined dynamics such as masculinist sentiment, internalisation of homosexuality fantasy, state power, and transcultural barriers, shaped and disciplined fan identity construction, introduced new metrics of recognising fans, and triggered the creation of alternative types of fans, followed by an updated multi-layered pyramid of fan hierarchy. This research therefore makes a noteworthy contribution to existing fan culture literature by offering a wealth of empirical insights and shedding light on fans’ self-contradiction regarding identity construction intertwined with gender, ideology hegemony, cultural legitimacy, and state power.